Statistical Analysis of Snow Cover Characteristics in the Middle Zagros Region - Moslem Seidy Shahivandi; Kamal Omidvar (Nīvār)
One of the most important forms of precipitation in the hydrological cycle of mountainous regions is snow. In this research, after collecting statistics and information related to days with snow during the statistical period (1989-2018) in stations located in the three provinces of Kermanshah, Ilam and Lorestan. Also, the time distribution and frequency of snowy days and their change process were discussed monthly and annually, In order to reveal the trend of annual changes in snowy days, Man-Kendall trend determination tests and Sen's slope estimator were investigated. These tests were carried out for the 30-year time series examined on an annual and monthly scale. The results snow days trend in Middle Zagros showed that the snow days have changed during the statistical period of the study, that the highest and lowest changes correspond to the highest and lowest frequency of snowy days in the studied region, In fact, the southeastern and northeastern regions of the region, which had the highest number of snowy days, have also had the greatest changes. In general, based on the results of the investigation of the trend of snow days in the Middle Zagros, it can be stated that the number of snow days in the study area has a decreasing trend, and this decreasing trend in some stations and some series (months of January and series annually), has become significant at the 95% confidence level. Based on the Sen's slope estimator method, the changes of snow days in the region are noticeable and significant